The Behavior and Effects from On-line Game Play Affected to Studying of College Students in Northern Region - เมฆพัฒน์ และคณะ, สุชาดา (Academic Journal of Thailand National Sports University, 2010)
The purpose of this research was to study the on-line game playing behavior and the effects from on-line game play affected to studying of college students in Northern Region. The research was later taken to be the guide linc in adjusting and developing the students on-line game playing bchavior more - properly. The subjects were 1,387 attending students in 15 colleges in Northern region. The tools were close-ended and open-ended questionnaires, and five-scales rating questionnaires. When the data was collected, the 1,158 perfect questionnaires were returned and calculated for 83.49. Then the data was analyzed to calculate for percentage, mean and standard deviation. On - linc game playing behavior of on - line game playing students, sort out by their behavior as following 1.1 Reasons for beginning in on - line game playing Most 48.2% began to play on-line game because they themselves desired to play, 36.3% played by their friends' advise, and 15.5% played for another reasons 1.2 Periods in on - line game play beginning Most 32.2% have played on - line games for 6 - 10 years, orderly, 18.6% have played for 1 - 5 years, 17.8% have played for 6 - 12 months, 8.9% have played for 1 - 5 months, 8.0% started to play, 7.4% have played for more than 10 years, and 7.1% have played for another period 1.3 Time spaces of on-line game playing Most 34.5% played on - line game during 8.00-12.00 p.m., orderly, 25.9% played during 4.00 -8.00 p.m. , 18,2% played during 12.00 p.m. - 4.00 am., 12,6% played during 12.00 am. - 4.00 p.m. , 7.0% played during 8.00 - 12.00 a.m. , and 1.8% played during 4.00 - 8.00 am. 1.4 Times spending in playing on - line garne, Most 36.9% spent more than 4 hours for each time in playing on - line game, orderly, 32.4% spent 3- 4 hours for each time in playing, 20.9% spent 2- 3 hours for each time in playing, and 9.8% spent 1 - 2 hours for each time in playing 1.5 How students played games in the past skill, Most 35.1% played on - line game everyday, orderly, 32.2% played every other day, 16.6% played for some days, 9.7% scarcely played, and 6.4% played in another ways 1.6 Days and times in on-line games playing Most 39.3% played on - line games after the class on weekdays, orderly, 27.6% played on weekends, 13.4% played on holidays, 10.5% played on special holidays or royal holidays, and 9.2% played on another days 1.7 The number of hours spending in on-line game playing per week Most 38.5% spent 15 - 20 hours per week in on - line game playing, orderly, 37.4% spent 10 - 15 hours per week in on-line game playing, 9.9% spent 5 - 10 hours per week in on - line game playing, 7.6% spent more than 20 hours per week in on - line game playing, and 6.6% spent less than 5 hours per week in playing game 1.8 Places in playing on - line game Most 44.8% played on - line game at the service shop, orderly, 31,3% played at their own house, 12.9% played at department store, 8.2% played in another places, and 2.8% played at friends' houses 1.9 Persons who played game with Most 49.3% played on-line game with friends, orderly, 32.1% played alone, 9.3% played with another people, 6.8% played with brothers and sisters, and 2.5% played with parents 1.10 Types of favorite on - line game Most 23.8% preferred to play sport on-line game, orderly, 18.7% preferred to play action on - line game, 13.9% preferred to play role - playing game, 13.5% preferred to play adventure game, 13.4% preferred to play simulation game, 10.3% preferred to play Hybrid game, and 6.4% preferred to play strategy game 1.11 Costs in on - line game Most 40.5% have costs in on-line game playing for internet, orderly, 34.7% paid for service charge of the on-line game play to service charge, 17.5% paid for internet service charge in case of playing at home, 4.4% paid for free of charge internet (of TOT), and 2.9% have no expense 1.12 Choices in filling up money for service from Air - time on - line game service owner Most 42.4% chose to fill up money for service charge of 20 hours (89 Baht), orderly, 39,0% chose to fill up money for 40 hours(159 Bahl), 10.6% chose to fill up money for 30 days (349 Baht), and 8.0% chose to fill up money for 15 days(189 Baht) 1.13 Advantages for on-line game playing Most 36.6% replied that on - line game playing provided amusing and entertaining, orderly, 30.4% relaxed tension, 12.9% got more friends, 6.3% encouraged Creative idea, 5.2% got more experiences, 4.3% allowed leisure time to be useful, 2.9% gained learning skills, and 1.4% exchanged opinions 1.14 Disadvantages of on - line game playing Most 23.9% replied that on - line game playing lost attention in studying, orderly 16.6% lost money, 14.5% used up health, 12.0 % less friends, 11.7% sted times, 8.2% nonsense, 5.4% easily be deceived 4.8 % lost the future life, and 5.4% game addicted 1.15 Problems risked from on - line game playing Most 19.9% replied that problem in studying risked up and led to not able to finish in curriculum period, orderly, 23,8% lacked of responsibility, 11.9% aggressive and violent, 10.2% be occupied with garnes, 8.6% lost mental health, 10.5% bad behavior led to tricking and criminals, 10.3% originated criminal problems, and 4.8% too expensive service charge On - line game playing affected students' Learning. Most agreed that on-line game playing totally affected students Icarning in the most level (X = 3.91) except item 4, on-line game playing caused not enough time (80 %) Item 6, on - line game playing caused not catching friends in class, and item 10, on - line game playing caused not able to finish the course in curriculum pcriod, that were in the middle level.